2023
DOI: 10.1109/access.2023.3258439
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Detection and Precision Spraying of Corn and Weeds Using the Improved YOLOv5 Model

Abstract: Date of publication xxxx 00, 0000, date of current version xxxx 00, 0000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…This algorithm is an open-source real-time image object detection system that uses a single convolutional neural network (CNN) pre-trained with the COCO dataset. The pre-trained weight model YOLOv5s.pt was selected because, in the work developed by [29], the YOLOv5s.pt model showed better performance over the other models of the Yolo-v5 family when used on the same crop. Additionally, in the work of [33], the author states that the models YOLO-v5n and YOLO-v5s showed advantages in inference times, being faster than YOLO-v4 but with lower accuracy, and concluded that all YOLO models, especially YOLO-v5n and YOLO-v5s, have shown great potential for real-time weed detection, and increased data could improve detection accuracy.…”
Section: Training Configuration Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…This algorithm is an open-source real-time image object detection system that uses a single convolutional neural network (CNN) pre-trained with the COCO dataset. The pre-trained weight model YOLOv5s.pt was selected because, in the work developed by [29], the YOLOv5s.pt model showed better performance over the other models of the Yolo-v5 family when used on the same crop. Additionally, in the work of [33], the author states that the models YOLO-v5n and YOLO-v5s showed advantages in inference times, being faster than YOLO-v4 but with lower accuracy, and concluded that all YOLO models, especially YOLO-v5n and YOLO-v5s, have shown great potential for real-time weed detection, and increased data could improve detection accuracy.…”
Section: Training Configuration Parametersmentioning
confidence: 99%
“…In a corn crop, [28] used aerial images for weed detection using the versions of YOLO v4 and v5, obtaining a mAP of 73.1% with YOLO-v5s and 72.0% with YOLO-v4. In [29], he built a precision spraying robot for corn cultivation using the different versions of YOLO-v5, and as a result, he obtained a mAP of 89.4%; despite the fact that he did not obtain the best performance, his processing time was less than the other versions. In the work of [30], he built a robot for the elimination of weeds with a blue laser in corn seedlings, and he used the YOLOX version as the detection method, obtaining an average detection rate of 92.45% for corn and 88.94% for weeds.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the test accuracy of C-DenseNet reached 97.99%. Wang et al (2023) used an algorithm based on improved YOLOv5s for recognizing corn and weeds in the field. The results indicated that the AP value of corn reached 96.3%, and the AP value of weeds reached 88.9%.…”
Section: Introductionmentioning
confidence: 99%
“…This approach segments high-resolution images into pertinent subgraphs through overlap rate calculations, employing multi-scale training techniques to attain accuracy and recall rates of 0.9465 and 0.9017, respectively. In addressing the issue of inadequate focus on crucial target features and noise feature suppression within the YOLOv5 model's feature extraction network, Wang et al [12] introduced the C3 Host bottleneck module and integrated an attention mechanism to improve the network's emphasis on relevant features. However, this model may mistakenly identify some wheat seedlings as weeds when processing them, so there remains potential for further enhancement in the feature extraction network.…”
Section: Introductionmentioning
confidence: 99%